EVALUASI PENGALAMAN PENGGUNA APLIKASI REDBUS MOBILE MENGGUNAKAN METODE USER EXPERIENCE QUESTIONNAIRE (UEQ) - Dicky Hidayat, Muhamad; Wahyudin (CV SWA Anugerah, 2025)
RedBus application is an online bus ticket booking platform that offers convenience for users in searching for schedules, booking tickets, and making payments. This study aims to evaluate the user experience of the RedBus Mobile application using the User Experience Questionnaire (UEQ) method. The User Experience Questionnaire (UEQ) is a method used to measure the user experience of a product’s quality based on six dimensions: Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The research method used in this study is a descriptive quantitative approach, where the results are presented in the form of explanations, with data collection through the distribution of UEQ questionnaires to RedBus users in the Indonesian bus mania community. The results of the study show that, in general, the RedBus application received good ratings from users, with the dimensions of Attractiveness, Perspicuity, Efficiency, Dependability, and Stimulation receiving an